THE RELEVANCE OF ISLAMIC APPROACH TO TRIBAL CRISIS IN KADUNA STATE - Umma Katume Dallami; Abubakar Muhammad Shitu (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2024)
This study "the relevant of Islamic teachings against ethnic unrest in Kaduna state" was motivated as a result of the unceasing political pandemonium that triggered numerous tribal feuds, religious and ethnic misunderstandings in Kaduna State, which have caused enormous loss of lives and wealth. In view of this, the research tends to examine the Islamic approach to tribal differences in relation to tribal crisis in Kaduna state, also to deliberate on the significance of discarding tribal differences to unity on the basis of Shari’ah guidance as relate to Kaduna State, and to assess the implications and challenges of upholding tribal differences as a basis of disunity in Kaduna state. For this, the research adopted survey research design where necessary data was collected. Kaduna State had over 50 tribes with over 6,113,503 populations and three Zones. 350 same questionnaires were administered in the three Zones for the three categories of respondents. 65 questionnaires were administered to academic scholars, where 59 questionnaires were retrieved. 85 questionnaires were administered to non-academic scholars, where 81 questionnaires were retrieved. Again 200 questionnaires were administered to public, where 193 questionnaires were retrieved. Simple percentage was used to analyze the data collected, which paved way for the discussion of the major findings of the research.; The research recommends that; Muslims should strictly adhere to the approach to tribal differences in relation to tribal crisis in Kaduna State of Islam for the enhancement of peaceful coexistence and Muslims scholars should emphasize preaching against unemployment or redundancy among Muslim youth in the State, and as well educate people about the essence of unity and the implication of tribalism in our localities.